Bakhtin in the Russian Ark - Solórzano Damasceno, Lara (2024)
This article delves into the depths of Russian Ark by Alexander Sokurov, where the grandeur of the Hermitage transforms itself into a stage for Bakhtin’s theories on chronotope, polyphony, and dialogism—concepts employed to analyze this film, where this inseparable unity of time and space emerges as a ‘house of time,’ where present, past, and future intertwine, offering a cyclical narrative in which Russian history is revived in a continuous, living flow. Each room of the museum, each filmed scene, is not merely a backdrop, but a voice resonating with centuries of ideologies and memories, creating a visual polyphony where times and values coexist.